Hardware-In-The-Loop Simulation Of Steer-By-Wire System In Automotive Vehicle - Mohd Zubir, Amir; Md Fahmi, Abd Samad (Institute Of Advanced Science Extension (IASE), 2016)
Field test approach of steer-by-wire (SBW) technologies by using actual vehicle can be very dangerous. This is due to the fact that stability of the vehicle is very sensitive to the steering wheel input. Less optimum parameters of the steering controllers or system failure may lead to dangerous road accident. In this study, hardware-in-the-loop simulation (HiLS) is used to bridge the gap between simulation and experimentation of SBW system. In the proposed HiLS system, SBW test rig is set up to communicate in real time with 14 degree-of-freedom vehicle model. Proportional-integral-derivative control optimized with Ziegler-Nichols method is used to control the stepper motor of the SBW test rig. From simulation and experimental results, SBW system developed has the ability to closely follow the steering trajectory of the conventional steering system with acceptable errors. By using HiLS, both controller algorithm and the functionality of the steering actuator of SBW system can be tested in a semi-real driving condition as preliminary testing.